AMTSAL OF THE QUR'AN IN DAKWAH: ACTUALIZATION OF QUALITY HUMANS BASED ON SURAH IBRAHIM: 24-25 - Kuswati Kuswati (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
One of the language styles conveyed by Allah through the Qur'an is in the form of parables (amtsal al-Qur'an). This form becomes interesting as it presents something abstract into a real form, by analogizing objects or situations that have similarities. No doubt that the language style with this example gives a beautiful impression and makes an impression. With the inseparability of three things; dakwah, communication, and language, the delivery of information packaged in the form of an example becomes something important and has many benefits for mad'u. Allah exemplifies quality humans in Surah Ibrahim/14: 24-25 with a good tree where the tree is one of Allah's creations that is close to humans. Quality humans are good quality humans, who are described as trees with strong roots, branches soaring to the sky and can be harvested at any time. The actualization of this example illustrates the condition of quality human beings who have a solid creed, because this creed is the basis for implementing God's rules. Always do good and benefit others wherever and whenever we are. Salah satu gaya bahasa yang di sampaikan Allah melalui al-Qur’an adalah dengan bentuk perumpamaan (amtsal al-Qur’an). Bentuk ini menjadi menarik karena menghadirkan sesuatu yang abstrak menjadi bentuk nyata, dengan cara menganalogikan benda atau keadaan yang memiliki keserupaan. Dan tidak dipungkiri gaya bahasa dengan permisalan ini memberi kesan yang indah dan membekas. Dengan tidak bisa dipisahkannya tiga hal yakni: dakwah, komunikasi dan bahasa, maka penyampaian informasi yang dikemas dalam bentuk permisalan menjadi sesuatu yang penting dan memiliki banyak manfaat bagi mad’u. Allah mempermisalkan manusia berkualitas dalam surah Ibrahim/14: 24-25 dengan sebuah pohon yang berkualitas baik di mana pohon adalah salah satu ciptaan Allah yang dekat dengan manusia. Manusia berkualitas adalah manusia yang bermutu baik, yang digambarkan sebagai pohon yang kuat akarnya, cabangnya menjulang ke langit dan dapat dipanen setiap saat. Aktualisasi permisalan ini menggambarkan kondisi manusia berkualitas adalah yang memiliki akidah yang kokoh, karena akidah inilah yang menjadi dasar melaksanakan aturan-aturan Allah. selalu berbuat kebajikan dan bermanfaat bagi orang lain di manapun dan kapanpun berada.